2020
DOI: 10.1159/000511736
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Steatosis Is Associated with Elevated Serum Iron in Patients with Obesity and Improves after Laparoscopic Sleeve Gastrectomy

Abstract: <b><i>Background:</i></b> Iron is closely related to metabolism. However, the relationship between iron and hepatic steatosis has not been fully elucidated. <b><i>Objective:</i></b> We aimed to investigate the triangular relationship between iron and hepatic steatosis and laparoscopic sleeve gastrectomy (LSG) in patients with obesity. <b><i>Methods:</i></b> A total of 297 patients with obesity and 43 healthy individuals with a normal BMI w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 23 publications
(29 reference statements)
1
12
0
Order By: Relevance
“…For example, a cross-sectional study showed that the serum iron levels and the NAFLD prevalence had a negative correlation ( 16 ). Conversely, a recent study based on obese patients found that the severe NAFLD group had higher serum iron levels than the mild or moderate groups ( 39 ). Other studies suggested an irrelevant association between serum iron and NAFLD staging and liver fat content ( 17 , 18 ).…”
Section: Discussionmentioning
confidence: 97%
“…For example, a cross-sectional study showed that the serum iron levels and the NAFLD prevalence had a negative correlation ( 16 ). Conversely, a recent study based on obese patients found that the severe NAFLD group had higher serum iron levels than the mild or moderate groups ( 39 ). Other studies suggested an irrelevant association between serum iron and NAFLD staging and liver fat content ( 17 , 18 ).…”
Section: Discussionmentioning
confidence: 97%
“…Bariatric surgery is one of the most effective methods to reduce body weight as well as improve metabolism (13)(14)(15). However, findings regarding change in VA after bariatric surgery has been inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic sleeve gastrectomy (LSG) is one of the most effective methods to treat obesity as it not only led to decreased bodyweight but also improved metabolism (13)(14)(15). The effects of LSG on VA levels are inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond anemia, aberrant iron levels contribute to hepatic injury, lipid peroxidation, and NAFLD severity. 48,73 Ma et al 74 reported increased iron overload in obese/ overweight patients with more severe NAFLD compared with subjects with normal body mass index (BMI) or mild to moderate NAFLD. Iron levels were also significantly higher in patients with dyslipidemia, hypertension, and hyperuricemia.…”
Section: Vitamin Ementioning
confidence: 99%
“…The researchers reported significant positive correlations between iron and BMI, ALT, serum triglycerides, fasting insulin, postprandial glucose, serum-free fatty acids, and hepatic steatosis. 74 Both impaired iron and vitamin E (a-tocopherol) levels were linked to hepatic steatosis pathology within a genetic hemochromatosis murine model. 75 Intriguingly, a genetic model of anemia promoted earlyonset NAFLD, accompanied by elevated serum ALT and triglycerides, 76 suggesting a role for iron deficiencies and hepatic steatosis.…”
Section: Vitamin Ementioning
confidence: 99%